Options, futures, and other derivatives - Hull, John, 1946- (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2006)
The book is about derivatives which is known as the bible in trading rooms through out the world. It also provides a comprehensive treatment of derivatives and risk management
Includes bibliographical references and index.
opc 23/02/15
Loans
Keywords: Futures; Stock options; Derivative securities